O prevladovanju estetskega nad poučnim v mladinski književnosti - Haramija, Dragica (Jezik in slovstvo, 2014)
Helga Glušič takes the standpoint that, in quality youth literature, ethics and aesthetics should take priority over pedagogical goals. In her research, she primarily pursues two aspects: the process of relieving youth literature of pedagogical elements, and play (its subject matter and/or formal element) and humour as two important elements of this kind of literature. By advocating the artistic value of a literary work as more crucial than its pedagogical usefulness, Glušič was among the first to establish a standard for the evaluation of youth literature that is still valid today.
Keywords: Glušič, Helga, 1934-2014; mladinska književnost; young adult literature; igra; humor; humour; estetika v literaturi